ANALISIS PEMANFAATAN SUMBER BELAJAR BERDASARKAN KERANGKA AECT PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Qondias, Dimas; Awe, Ermelinda Yosefa; Moi, Maria Yulita; Jodho, Maria Nio (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aims to analyze the use of learning resources in Grade IV Pancasila Education instruction at SDN Hedhazita based on six learning-resource components proposed by AECT, namely messages, people, materials, tools, techniques, and environment. The study employed a descriptive qualitative approach. Data were collected through classroom observations across six instructional meetings, semi-structured interviews, and documentation. The research participants included a Pancasila Education teacher and 22 Grade IV students. Data were analyzed through data reduction, data display, and conclusion drawing/verification by mapping the findings onto the AECT components. Data trustworthiness was strengthened through methodological and source triangulation, as well as limited member checking with the teacher. The findings indicate that the use of learning resources tended to rely predominantly on people and the environment. Active learning techniques such as group discussions, role-playing, and simulated deliberation supported student engagement and understanding of Pancasila values. The main challenges identified included limited use of media/technology and the dominance of printed materials. These findings highlight the importance of strengthening the integration of learning resources and school support to enhance more contextual and participatory Pancasila Education learning.